Performa Bisnis E-Commerce PT XYZ - Aliyansyah, Fariz; Susanto, Yulius Kurnia (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
Internship activities at partner company PT XYZ, are activities carried out to provide a forum for interns to contribute to the company's business activities, especially retail companies. The work that has been done for approximately five months. The benefits of internships ranging from technical skills on the tools used during work, to the ability of soft skills and also hard skills that are honed during internships at PT XYZ. then with some of the evaluations contained are expected to be able to become material developments for the organizers, participants to company partners in internships.